Feudal America Elements of the Middle Ages in Contemporary Society - Shlapentokh, Vladimir (Penn State University Press, 2011)
Do Americans live in a liberal capitalist society, or a society in which big money, private security, and personal relations determine key social outcomes? Shlapentokh and Woods argue that the answer to these questions cannot be found among the conventional models. Offering a new analytical tool, the authors present a provocative explanation of the nature of contemporary society by comparing its essential characteristics to those of medieval European societies. Their feudal model emphasizes five elements: the weakness of the state to protect its citizens, conflict and collusion between and within organizations that involve corruption and other forms of illegal or semilegal actions, the dominance of personal relations in political and economic life, the prevalence of an elitist ideology, and the use of private agents and organizations to provide safety and security. Feudal America urges readers to look for explanations of contemporary social problems in medieval European history.